IoT-based Monitoring System for Energy Consumption Costs from Battery Supply - Hakim, Muhammad Fahmi; Kusuma, Wijaya; Suudi, Ismail; Ridzki, Imron; Setiawan, Awan; Syamsuri, Tresna Umar (Universitas Syiah Kuala, 2024)
A battery must be monitored in real-time to ensure it meets its designed lifetime. Additionally, energy costs from the battery supply must be calculated and controlled to enable solar power plant entrepreneurs to profit practically. This project aims to develop an IoT-based monitoring and controlling system for battery conditions, especially energy consumption costs from battery supply. This system uses an ESP32 microcontroller, INA219 sensor, single channel 5 VDC optocoupler relay, and OLED display. The ESP32 processes the current and voltage from the INA219 sensor and then displays on the OLED display. The parameters displayed include consumed energy costs, current, voltage, power, consumed energy, and used battery capacity. Data is also sent to the Blynk website using IoT, allowing these parameters to be monitored in real time. Based on test results, the average error in calculating energy costs is 0.046%, and other measured or calculated parameters are below 1%. This system can also turn the power flow to the load on and off using the Blynk platform. It can be concluded that the system works well, enabling IoT-based monitoring and control of battery parameters.